Cardiac Syndrome X: Advances in Treatment for Chest Pain without Artery Stenosis - Tulej, Dawid; Furtak, Daria; Dziedzic, Alicja; Niewiadomska, Jagoda; Marko, Natalia; Grela, Wiktor; Głogowska, Paulina; Marciniuk, Dominika; Górska, Aleksandra; Gniaź, Natalia (Journal of Education, Health and Sport, 2024)
The number of patients diagnosed with Cardiac Syndrome X continues to increase. This condition is marked by anginal pain despite the absence of abnormal findings on coronary angiography or coronary spasm. It is considered a form of ischemic heart disease, with its incidence being most common among women in the perimenopausal and postmenopausal stages. The aim of this article is to review therapeutic options for Cardiac Syndrome X. The most effective treatments commonly used include calcium channel blockers and beta-blockers, including newer generation options that promote vasodilation in the endothelium. Angiotensin-converting enzyme (ACE) inhibitors are also frequently used to enhance therapeutic outcomes. Other medications used were nitrates, statins, ranolazine, imipramine, nicorandil, aminophylline, cilostazol, sildenafil, fasudil. Emerging theories suggest altered pain perception, potentially involving heightened neural sensitivity, may significantly contribute to the symptoms in CSX. Additionally, studies indicate that vitamin D supplementation, often beneficial for cardiovascular health, may alleviate symptoms in CSX. Non-pharmacological methods also have proven efficacy, such as Enhanced External Counterpulsation, spinal cord stimulation and transcutaneous electrical nerve stimulation. Lifestyle changes and (CBT) also play a crucial role in the comprehensive management of Cardiac Syndrome X (CSX), targeting factors that pharmacological treatments alone may not address.